Social and Material Adversity from Adolescence to Adulthood and Allostatic Load in Middle-Aged Women and Men: Results from the Northern Swedish Cohort - Gustafsson, Per E. (Springer-Verlag, 2011)
BACKGROUND: Little is known about the theoretically assumed association between adversity exposure over the life course and allostatic load in adulthood. PURPOSE: This study aims to examine whether social and material adversity over the life course is related to allostatic load in mid-adulthood. METHODS: A 27-year prospective Swedish cohort (N = 822; 77% response rate) reported exposure to social and material adversities at age 16, 21, 30 and 43 years. At age 43, allostatic load was operationalized based on 12 biological parameters. RESULTS: Social adversity accumulated over the life course was related to allostatic load in both women and men, independently of cumulative socioeconomic disadvantage. Moreover, social adversity in adolescence (in women) and young adulthood (in men) was related to allostatic load, independently of cumulative socioeconomic disadvantage and also of later adversity exposure during adulthood. CONCLUSION: Exposure to adversities involving relational threats impacts on allostatic load in adulthood and operates according to life course models of cumulative risk and a sensitive period around the transition into adulthood. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12160-011-9309-6) contains supplementary material, which is available to authorized users.